Impact of engaging in fitness on psychological sphere of women - Шишкіна [Shishkina O.], О. М. (Slobozhanskyi Herald of Science and Sport, 2012)
Research carried out to find out of taking up of fitness on the psychology-physiological sphere of women. It is set that engaging in fitness are caused by the decline of sensitiveness to the crisis, level of display of professional stress, subjective perception of symptoms of diseases of heart, stomach and joints. At these persons intensity of complaints diminishes for the personal health. With the persons engaging fitness relationships get better with other persons, they feel their support, a self-appraisal, level of being aptimistic, rises for them, at the simultaneous decline of tension and degree of display of negative emotions